MARKETING ACTIVITY IN ROMANIAN MICROCREDIT ORGANIZATIONS - Savescu Roxana Florenta (Annals of the University of Oradea: Economic Science, 2012)
Microfinance is the solution that ensures the provision of loans and other basic financial services to those entrepreneurs who have limited access to the banking sector. These financial services provided by microfinance institutions allow small business owners to take advantage of their entrepreneurship skills by developing small businesses capable of generating additional income. As they mature, Romanian microcredit organizations become gradually aware of the importance of marketing in their current activities. The paper presents the results of a qualitative research on the experience and marketing practices in major microfinance institutions in Romania, highlighting at the same time the factors influencing decisions to invest resources in this area. The conclusions of the research reveal that microcredit organizations have a limited institutional capacity to develop complex marketing programs that drive marketing activities and resources to achieve the objectives of the organization. The approach here is one of a reactive management, the situations that pushes microcredit organizations into engaging in some marketing activities and using various instruments being determined by changes in the structure and level of market development and competition or by the availability of funds for current activity. Although marketing interventions should be considered important on all markets, the truth is that different types of markets (emerging, developing, mature markets) require certain marketing activities. The proposed marketing mix contains 8 elements ("8 P") that ought to be optimally combined within the marketing strategy, in order to get the expected response from the target group: product, price, placement, promotion, processes, procedures, personnel, partnership. The topic chosen for this paper answers a need for know-how in the Romanian microcredit organizations, in terms of their marketing activity. From a scientific point of view, the paper has a pioneering role, representing the first steps taken in Romania towards the in-depth study of the field of microfinance and of marketing in the microcredit industry.